2022
DOI: 10.3390/v14030524
|View full text |Cite
|
Sign up to set email alerts
|

DOLAVI Real-Life Study of Dolutegravir Plus Lamivudine in Naive HIV-1 Patients (48 Weeks)

Abstract: Brief: Real-world data in naïve HIV-1 patients demonstrate that dolutegravir plus lamivudine in a multiple tablet regimen is effective, safe, and satisfactory; it causes moderately increasing weight and abdominal circumference and is administrable on a test-and-treat strategy. Background: Our objectives were to determine the real-life effectiveness and safety of DT with dolutegravir (50 mg/QD) plus lamivudine (300 mg/QD) in a multiple-tablet regimen (MTR) in naïve PLHIV followed up for 48 weeks and to evaluate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Viruses 2022, 14, 2626 2 of 10 Two-drug regimens (2DRs) have been studied as a means of minimizing short-and longterm antiretroviral (ARV) toxicity in naive or ARV-experienced patients [3]. They include the combination of lamivudine and dolutegravir (DTG), which achieved excellent outcomes in clinical trials in naive [4][5][6] and treatment-experienced patients [7][8][9]. A 2DR with rilpivirine (RPV) plus DTG demonstrated the same effectiveness in treatment-experienced patients as that obtained with three-drug regimens (3DRs) in two clinical trials, SWORD 1 and 2, which found no risk of increased resistance and improvements in renal function and bone metabolism [10].…”
Section: Introductionmentioning
confidence: 99%
“…Viruses 2022, 14, 2626 2 of 10 Two-drug regimens (2DRs) have been studied as a means of minimizing short-and longterm antiretroviral (ARV) toxicity in naive or ARV-experienced patients [3]. They include the combination of lamivudine and dolutegravir (DTG), which achieved excellent outcomes in clinical trials in naive [4][5][6] and treatment-experienced patients [7][8][9]. A 2DR with rilpivirine (RPV) plus DTG demonstrated the same effectiveness in treatment-experienced patients as that obtained with three-drug regimens (3DRs) in two clinical trials, SWORD 1 and 2, which found no risk of increased resistance and improvements in renal function and bone metabolism [10].…”
Section: Introductionmentioning
confidence: 99%
“…Results from the test-and-treat subgroup in TANDEM are in alignment with those from the phase 3b test-and-treat STAT clinical trial, in which 82% of participants in the ITT-E missing = failure analysis achieved virologic suppression at week 48. In a single-arm, multicenter, prospective trial in Spain, 76 (86%) of 88 treatment-naive people initiating DTG + 3TC within 1 week of initial consultation achieved HIV-1 RNA < 50 copies/ml at week 48 [ 19 ]. In a retrospective analysis of the REDOLA cohort in Spain, 111 (84%) of 132 treatment-naive people initiating DTG/3TC without availability of baseline resistance testing results had HIV-1 RNA < 50 copies/ml at week 96 [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…An observational study of treatment-naive individuals in China who initiated DTG/3TC reported that 96% of 22 people with baseline viral loads ≥ 500,000 copies/ml achieved HIV-1 RNA < 50 copies/ml at week 48 [ 21 ]. In a single-arm, multicenter, prospective trial in Spain that included 17 treatment-naive individuals with baseline viral loads > 100,000 copies/ml, 14 (82%) achieved HIV-1 RNA < 50 copies/ml at week 48 [ 19 ]. Lastly, in a retrospective analysis of the REDOLA cohort in Spain, 39 (87%) of 45 people with baseline viral loads ≥ 100,000 copies/ml had HIV-1 RNA < 50 copies/ml at week 96 [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two other cohorts have assessed this rapid treatment approach. At 48 weeks after starting first-line ART, Hidalgo-Tenorio et al found an effectiveness of 86% among 88 patients who started dolutegravir/lamivudine in the first week after their first specialist consultation, 8 and Cabello et al found an effectiveness of 85% among 135 patients, 72% of whom did not have the results of resistance testing available at the start of treatment; 7 neither cohort compared dolutegravir/lamivudine treatment effectiveness with 3DRs.…”
Section: Discussionmentioning
confidence: 99%